The anuran calling repertoire in the light of social context - Toledo, Luis Felipe; Martins, Itamar A.; Bruschi, Daniel P.; Passos, Michel A.; Alexandre, Cesar; Haddad, Celio Fernando Baptista [UNESP] (Springer, 2015)
Frogs are immediately associated to their conspicuous vocalizations emitted during the breeding season. Therefore, many scientists were inspired to study their acoustic communication. Nowadays, many types of calls are described and we felt the need of reviewing the terminology currently and historically applied. As a result, we proposed the classification of anuran vocalization into three major categories: reproductive, aggressive, and defensive calls. These categories are subdivided according to the social context of emission mostly reflecting also acoustic differences among call types. Some call types are here proposed to be synonymies of the mostly used and inclusive terms. We also suggest terminologies for basic bioacoustical analyses, mostly applied in call descriptions. Furthermore, we present cases of complex calls, including call gradation. Finally, based on novel data (such as an unusual case of juvenile vocalizations), we discuss situations in which it is difficult to classify call types, reflecting the need of experimental studies.
Keywords: Calling activity; Vocal behavior; Social communication; Bioacoustics; Categorization